2022
DOI: 10.1213/ane.0000000000005925
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Con Debate: Do We Need Quantitative Neuromuscular Monitoring in the Era of Sugammadex?

Abstract: In this Pro-Con article, we debate the merits of using quantitative neuromuscular blockade monitoring. Consensus guidelines recommend their use to guide the administration of nondepolarizing neuromuscular blockade and reversal agents. A major impediment to this guideline is that until recently, reliable quantitative neuromuscular blockade monitors have not been widely available. Without them, anesthesia providers have been trained with and are adept at using a variety of qualitative neuromuscular blockade moni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…The 2018 Expert Consensus states that objective neuromuscular monitoring must be performed whenever non-depolarizing neuromuscular blocking agents are used, and that quantitative monitoring is used to guide the use of non-depolarizing muscle relaxants intraoperatively and to reduce the incidence of residual neuromuscular blockade [4,5]. The 2021 British Anaesthesia Society guidelines suggest that the use of continuous head elevation, eye opening on exhalation and tongue depressor tests to assess residual neuromuscular blockade is inadequate and that these modalities are only 30%-50% sensitive with a positive predictive value of less than 50% [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2018 Expert Consensus states that objective neuromuscular monitoring must be performed whenever non-depolarizing neuromuscular blocking agents are used, and that quantitative monitoring is used to guide the use of non-depolarizing muscle relaxants intraoperatively and to reduce the incidence of residual neuromuscular blockade [4,5]. The 2021 British Anaesthesia Society guidelines suggest that the use of continuous head elevation, eye opening on exhalation and tongue depressor tests to assess residual neuromuscular blockade is inadequate and that these modalities are only 30%-50% sensitive with a positive predictive value of less than 50% [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that only 17% of anesthesiologists choose to use objective monitoring. However, studies have shown that only 17% of anesthesiologists choose to use objective monitoring, while the majority of anesthesiologists choose to use subjective judgement [4,5]. Though objective monitoring can reduce the incidence of postoperative residual neuromuscular blockade from 62% to 4%, objective monitoring is di cult to use in clinical practice [6].…”
Section: Introductionmentioning
confidence: 99%
“…With such a strategy, a compliance greater than 90% can be achieved in documenting the minimally acceptable degree of neuromuscular recovery (TOF ratio >90) before tracheal extubation. 11 Despite a still ongoing (and poorly defended) argument against the routine use of quantitative monitors, 12 there is irrefutable evidence that quantitative monitoring must become routine. 5 For other currently accepted routine monitoring modalities such as pulse oximetry and end-tidal CO 2 monitors there is no evidence that they affect patients' outcomes.…”
mentioning
confidence: 99%
“…I n this issue of Anesthesia & Analgesia, Blobner et al 1 present an erudite debate about the value of quantitative neuromuscular monitoring in a modern clinical practice that includes the selective relaxant binding agent, sugammadex. The article provides an interesting and educational debate, clearly designed to expose the reasons behind clinicians' decisions to use quantitative neuromuscular monitors (Pro section) or to avoid their use (Con).…”
mentioning
confidence: 99%
“…Belief that routine administration of sugammadex supplants the need for monitoring. In the "con" section of the debate, 1 the authors stated that monitoring is not needed in the era of sugammadex, since its reversal is "fast and effective." However, sugammadex is 3× more selective for rocuronium than for vecuronium.…”
mentioning
confidence: 99%